2018
DOI: 10.9734/ajpas/2018/v2i124559
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Nigeria’s Economic Growth Rate: A Probability Distribution Fitting Approach

Abstract: This study examined the probability distribution that best described the quarterly economic growth rate of Nigeria between 1960- 2015. The study collected secondary data from Central Bank of Nigeria (CBN) Statistical Bulletin 2015 on Gross Domestic Product to compute the economic growth rate of Nigeria. Six theoretical statistical distributions were fitted via Normal Distribution, Logistic Distribution, Laplace Distribution, Cauchy Distribution, Gumbel (Largest Extreme Value) Distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…The findings by Eke et al (2018) diverge slightly from Awe and Gil-Alana's (2019). Using a probability distribution fitting approach, they analysed data spanning 55 years from the CBN's Statistical Bulletin on GDP to calculate Nigeria's GDP growth rate.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings by Eke et al (2018) diverge slightly from Awe and Gil-Alana's (2019). Using a probability distribution fitting approach, they analysed data spanning 55 years from the CBN's Statistical Bulletin on GDP to calculate Nigeria's GDP growth rate.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…They fitted six theoretical statistical distributions using normal distribution, logistic distribution, Laplace distribution, Cauchy distribution, Gumbel distribution and generalized logistic distribution. Eke et al (2018) found that the mean quarterly economic growth rate was 4.75% for the period 1960 to 2015. They computed the median value for the quarterly economic growth rate as 2.88% with their standard deviation from the mean estimated to be 11.30%.…”
Section: Descriptive Statisticsmentioning
confidence: 99%